PENILAIAN TEKNOLOGI MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS DAN TEKNOMETRIK DI DEPARTEMEN PRODUKSI - Cahyono, Didik Eko; Wahyuni, Hana Catur (Universitas Muhammadiyah Surakarta, 2015)
Company that will conduct business development needs identification of technology needed, so that development can be in accordance with company objectives. Therefore it is necessary to evaluate the existing technological sophistication.The purpose of this study was to determine the level of sophistication of the individual components of the technology (technoware, humanware, infoware, orgaware) and determine which technology components into a development priority. This study used Analytical Hierarchy Process (AHP) and technometric. Based on the results obtained after performing calculations with AHP and technometric, found that the level of technology component sophistication in the company according to technoware is 0.650, humanware is 0.557, infoware is 0.637, orgaware is 0.693 and the overall level of sophistication or Total Contribution Coefficient (TCC) is approximately 62%. At the current, level of technology at PT XYZ is semi-modern. While the most important technological components to be developed are technoware and lowest component technologies are humanware.